Genomic Characterization of Endemic and Ecdemic Non-typhoidal Salmonella enterica Lineages Circulating Among Animals and Animal Products in South Africa - Carroll, Laura M.; Pierneef, Rian; Mathole, Masenyabu; Matle, Itumeleng (Frontiers in Microbiology, 2021)
In Africa, the burden of illness caused by non-typhoidal Salmonella enterica is disproportionally high; however, whole-genome sequencing (WGS) efforts are overwhelmingly concentrated in world regions with lower burdens. While WGS is being increasingly employed in South Africa to characterize Salmonella enterica, the bulk of these efforts have centered on characterizing human clinical strains. Thus, very little is known about lineages circulating among animals in the country on a genomic scale. Here, we used WGS to characterize 63 Salmonella enterica strains isolated from livestock, companion animals, wildlife, and animal products in South Africa over a 60-year period. Genomes were assigned to serotypes Dublin, Hadar, Enteritidis, and Typhimurium (n = 18, 8, 13, and 24 strains, respectively) and sequence types (STs) ST10 (all S. Dublin), ST33 (all S. Hadar), ST11/ST366 (n = 12 and 1 S. Enteritidis, respectively), and ST19/ST34 (n = 23 and 1 S. Typhimurium, respectively; via seven-gene multi-locus sequence typing). Within-ST phylogenies were constructed using genomes sequenced in this study, plus publicly available genomes representative of each ST’s (i) global (n = 2,802 and 1,569 S. Dublin and Hadar genomes, respectively) and (ii) African (n = 716 and 343 S. Enteritidis and Typhimurium genomes, respectively) population. For S. Dublin ST10, a largely antimicrobial-susceptible, endemic lineage circulating among humans, animals, and food in South Africa was identified, as well as a lineage that was likely recently introduced from the United States. For S. Hadar ST33, multiple South African lineages harboring streptomycin and tetracycline resistance-conferring genes were identified. African S. Enteritidis ST11 could be primarily partitioned into one largely antimicrobial-susceptible and one largely multidrug-resistant (MDR) clade, with South African isolates confined to the largely antimicrobial-susceptible clade. S. Typhimurium ST19/ST34 strains sequenced here were distributed across the African S. Typhimurium ST19/ST34 phylogeny, representing a diverse range of lineages, including numerous MDR lineages. Overall, this study provides critical insights into endemic and ecdemic non-typhoidal Salmonella enterica lineages circulating among animals, foods, and humans in South Africa and showcases the utility of WGS in characterizing animal-associated strains from a world region with a high salmonellosis burden.